A conserved SNP variation in the pre-miR396c flanking region in Oryza sativa indica landraces correlates with mature miRNA abundance - Jaganathan, Deepa; Rajakani, Raja; Doddamani, Dadakhalandar; Saravanan, Divya; Pulipati, Shalini; Hari Sundar G, Vivek; Sellamuthu, Gothandapani; Jayabalan, Shilpha; Kumari, Kumkum; Parthasarathy, Pavithra; S, Punitha; Ramalingam, Sivaprakash; et al. (Scientific reports, 2023)
Plant precursor miRNAs (pre-miRNA) have conserved evolutionary footprints that correlate with mode of miRNA biogenesis. In plants, base to loop and loop to base modes of biogenesis have been reported. Conserved structural element(s) in pre-miRNA play a major role in turn over and abundance of mature miRNA. Pre-miR396c sequences and secondary structural characteristics across Oryza species are presented. Based on secondary structure, twelve Oryza pre-miR396c sequences are divided into three groups, with the precursor from halophytic Oryza coarctata forming a distinct group. The miRNA-miRNA* duplex region is completely conserved across eleven Oryza species as are other structural elements in the pre-miRNA, suggestive of an evolutionarily conserved base-to-loop mode of miRNA biogenesis. SNPs within O. coarctata mature miR396c sequence and miRNA* region have the potential to alter target specificity and association with the RNA-induced silencing complex. A conserved SNP variation, rs10234287911 (G/A), identified in O. sativa pre-miR396c sequences alters base pairing above the miRNA-miRNA* duplex. The more stable structure conferred by the 'A10234287911' allele may promote better processing vis-à-vis the structure conferred by 'G10234287911' allele. We also examine pri- and pre-miR396c expression in cultivated rice under heat and salinity and their correlation with miR396c expression.
Keywords: jednonukleotidový polymorfismus; halotolerantní rostliny; Oryza; Polymorphism, Single Nucleotide; Salt-Tolerant Plants; MicroRNAs; rýže (rod); mikro RNA